2019
DOI: 10.1590/abd1806-4841.20198321
|View full text |Cite
|
Sign up to set email alerts
|

Tissue healing efficacy in burn patients treated with 1% silver sulfadiazine versus other treatments: a systematic review and meta-analysis of randomized controlled trials

Abstract: This study aims to evaluate tissue healing efficacy in burn patients treated with 1% silver sulfadiazine versus other treatments. This is a systematic literature review and meta-analysis of randomized clinical trials performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) and PICO strategy, registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the number CRD42017081057. The review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The acticoat dressing can be kept for 3 days, so it was considered a good treatment option. Maciel et al (2019) reported that SP had shown excellent effectiveness as a bactericide, in addition to being well accepted by burn centres. Various products have been compared, such as aloe vera, aquacel, and centiderm, which have shown efficacy compared to SP, although it is considered too early to declare their efficacy.…”
Section: Antibacterial Ointmentsmentioning
confidence: 99%
“…The acticoat dressing can be kept for 3 days, so it was considered a good treatment option. Maciel et al (2019) reported that SP had shown excellent effectiveness as a bactericide, in addition to being well accepted by burn centres. Various products have been compared, such as aloe vera, aquacel, and centiderm, which have shown efficacy compared to SP, although it is considered too early to declare their efficacy.…”
Section: Antibacterial Ointmentsmentioning
confidence: 99%
“…No significant difference was found in the average wound-healing time, but Flaminal ® Forte was deemed advantageous due to Antibiotics 2020, 9, 90 3 of 24 less frequently required dressing changes [33]. Finally, a 2019 meta-analysis of 81 studies found that 11/11 studies that met the inclusion criteria of the review found silver sulfadiazine to be inferior to alternative treatments in the mean wound-healing time [34].…”
Section: Silvermentioning
confidence: 99%
“…No significant difference was found in the average wound-healing time, but Flaminal ® Forte was deemed advantageous due to Antibiotics 2020, 9, 90 3 of 24 less frequently required dressing changes [33]. Finally, a 2019 meta-analysis of 81 studies found that 11/11 studies that met the inclusion criteria of the review found silver sulfadiazine to be inferior to alternative treatments in the mean wound-healing time [34].In the last 20 years, some new classes of silver complexes have garnered attention for their antibacterial properties, in particular N-heterocyclic carbene (NHC) complexes of silver(I). A comprehensive summary of antimicrobial silver compounds can be found in several recent reviews [27,[35][36][37].…”
mentioning
confidence: 99%
“…For burn wounds, other alternative therapies are superior in another meta-analysis. 21 Silver sulfadiazine was also demonstrated to impair re-epithelialization more compared to nanosilver in a study comparing conjugated silver dressings. 22 The results show, albeit from a small sample size, a trend for advanced wound dressings to have betterwound outcomes compared to basic wound dressings.…”
Section: Head N=6mentioning
confidence: 99%